Spectroscopic studies of the interaction between phosphorus heterocycles and cytochrome P450 - Dumei Ma; Libo Zhang; Yingwu Yin; Yuxing Gao; Qian Wang (Elsevier, 2021)
P450 fatty acid decarboxylase OleT from Staphylococcus aureus (OleTSA) is a novel cytochrome P450 enzyme that catalyzes the oxidative decarboxylation of fatty acids to yield primarily terminal alkenes and CO2 or minor α- and β-hydroxylated fatty acids as side-products. In this work, the interactions between a series of cycloalkyl phosphorus heterocycles (CPHs) and OleTSA were investigated in detail by fluorescence titration experiment, ultraviolet-visible (UV-vis) and 31P NMR spectroscopies. Fluorescence titration experiment results clearly showed that a dynamic quenching occurred when CPH-6, a representative CPHs, interacted with OleTSA with a binding constant value of 15.2 × 104 M−1 at 293 K. The thermodynamic parameters (ΔH, ΔS and ΔG) showed that the hydrogen bond and van der Waals force played major roles in the interaction between OleTSA and CPHs. The UV-vis and 31P NMR studies indicated the penetration of CPH-6 into the interior environment of OleTSA, which greatly affects the enzymatic activity of OleTSA. Therefore, our study revealed an effective way to use phosphorus heterocyclic compounds to modulate the activity of cytochrome P450 enzymes.